Juego de Tronos: La tragedia de un Estado que debe funcionar entre los eventuales excesos de un Presidente con competencias reforzadas y las reacciones desproporcionadas de un Congreso incontrolable —y el rol que un Tribunal Constitucional puede cumplir al respecto— - Espinosa-Saldaña Barrera, Eloy (2021)
Peru has undergone a series of constitutional crisis in the last years which have brought to the attention of society the paramount importance of the Peruvian Constitutional Tribunal in Peruvian politics. The author, Justice of the Constitutional Tribunal, analyses two particular cases: the dissolution of Congress of 30 September 2019 and the impeachment trial of 9 November 2020, their constitutional implications and thevalidity of those actions inside the framework established by the Constitution; furthermore analysing the positions the Tribunal has adopted in the last years on the abilities of the Executive to propose motions of no confidence and in general the constitutional structure of the State relative to the separation of powers.